On the fatigue of steel catenary risers - Chibueze, Nnamdi Onochie (Strojniški vestnik, 2016)
Steel catenary risers (SCR), though an appropriate and cost effective tool for deepwater development, are fraught with difficult fatigue challenges derived from loads due to the actions of wind, wave and current. In this study, a model SCR-AB with end-A attached to floating production, storage and offloading vessels (FPSO) and end-B anchored to the seabed was created using OrcaFlex © finite element software. Also attached to this model is a 10 4 kg 6D buoy of 6 m height and volume 20 m%, which was fixed to the SCR at 900 m of the riser length. The various sections of the homogenous 2200 m long SCR pipe include 50 m flex joint section, 350 m strake length, 1300 m riser pipe length, and 500 m flowline section. Metrological ocean data, geotechnical data and SCR data were input into the model which was subjected to the Ochi-Hubble and Joint North Sea Wave Project (JONSWAP) wave spectra. Analyses to determine the influence of fatigue damage on the model was made using system simulation under both static and dynamic modes. The results for JONSWAP wave spectra showed the fatigue life of the SCR to be 1.8 years at the touch-down-point (TDP) while that of Ochi-Hubble wave spectra showed a fatigue life of 13.6 years at SCR TDP, differing by a factor of 7.5. Furthermore, the S-N curves obtained from both wave spectra corroborated an inverse relationship between Stress values S and the number of stress cycles to failure N on a log-log scale.
Keywords: Gvinejski zaliv; jeklene viseče dvižne cevi; JONSWAP; Ochi-Hubble; točka stika z morskim dnom; utrujanje